Language of assurance: The use of discourse markers in insurance policy documents - Ariffin, Kamisah; Mat Pardi, Khalid; Nordin, Noli Maishara; Rostam Affendi, Faiza; Rostam Affendi, Muhaizam (EDUCATUM Journal of Social Sciences, 2025)
The comprehensibility of insurance policy documents is an important issue but often overlooked. The lack of comprehensibility of the policy can cause misunderstandings and even disputes between insurance providers and policyholders. In the realm of legal texts of which insurance policy is a part of, discourse markers play an important role in enhancing or impeding the comprehensibility of the contents. The role of discourse markers within insurance policies has not been extensively studied. Thus, there is a significant research gap in exploring how these linguistic elements contribute to the comprehensibility of insurance policies, ergo, affecting readers’ comprehension. The study employed a mixed-method approach of quantitative and qualitative data analysis to examine the use of discourse markers in insurance policy documents and how they contribute to the policy's comprehensibility. The quantitative analysis involved the frequency counts of the use and distribution of the discourse markers in the policy documents. The qualitative analysis involved the analysis of data from a semi-structured interview that gauged the policyholders’ perceptions on their comprehension of the policy documents concerning the use of discourse markers. 839 discourse markers were identified based on six categories of discourse markers: contrastive, elaborative, inferential, temporal, conditional, and reference. Each category plays a specific role in shaping the narrative and ensuring the clarity of contractual details. The interview data indicate that familiar and common discourse markers could facilitate understanding, but complex and unfamiliar discourse markers might detract comprehension and readability.  The findings pointed out that the challenges of understanding the legal documents are observable across various groups of policyholders.  Insurers can resolve this by using more common and familiar discourse, making it more inclusive and comprehensible for all consumers.